Geography, human rights education and the socioeconomic bias in school space / A Geografia Escolar, a educação em Direitos Humanos e o preconceito socioeconômico no espaço escolar - Melse Vantuir dos Santos Medeiros; Júlio César Barbosa Santana; Jacqueline Praxedes de Almeida (Diversitas Journal, 2018)
This article presents the results of research on socioeconomic bias, held at school field training course by licenciandos of the course of Geography degree from the Federal University of Alagoas, in the discipline of supervised internship (IV). The research is characterized by being a study of qualitative nature, used as an instrument of data collection the questionnaire. The survey revealed, among other results, the existence of socioeconomic bias on the part of students. The work is a reflection on the teaching of geography and human rights education as agents combat-related values formers inequalities and social injustices. The research data helped the trainees to reflect on their role as agents capable of assisting in the promotion of a society that is less exclusionary.